2020
DOI: 10.1002/ygh2.384
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hepatic fibrosis stages after achieving SVR following direct‐acting anti‐viral treatment: a prospective study

Abstract: Summary Introduction Chronic hepatitis C (CHC) represents a major global health problem. The availability of direct‐acting anti‐virals (DAAs) allowed the treatment of many patients with liver cirrhosis (F4) and advanced hepatic fibrosis (F3). The impact of viral clearance following DAAs treatment on the natural history of liver cirrhosis is uncertain or not clearly evident in the literature as most studies were retrospective, including small number of patients and for short follow‐up duration; there is a need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 57 publications
(80 reference statements)
1
14
1
Order By: Relevance
“…Furthermore, the level of fibrosis and cirrhosis can change with the initiation of treatment and virus eradication. 20 Hence, our study suggests that an alternative, and potentially more efficient and cost-effective approach is an individualized risk-based surveillance strategy. If our results are independently confirmed, such a strategy would involve two GES and remained high post-GES, will need intense surveillance program which is important for early detection of HCC, followed by an early treatment which could increase patients' survival.…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, the level of fibrosis and cirrhosis can change with the initiation of treatment and virus eradication. 20 Hence, our study suggests that an alternative, and potentially more efficient and cost-effective approach is an individualized risk-based surveillance strategy. If our results are independently confirmed, such a strategy would involve two GES and remained high post-GES, will need intense surveillance program which is important for early detection of HCC, followed by an early treatment which could increase patients' survival.…”
Section: Discussionmentioning
confidence: 88%
“…Metabolic risk factors, such as metabolic syndrome, obesity, or insulin resistance, may further increase the risk of HCC through the presence of low-grade chronic inflammation ( 48 ). Furthermore, T2DM contributes to fibrosis progression after DAA therapy, which is a risk of HCC ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…An Egyptian study conducted by Shiha et al [ 32 ] showed the reversal of cirrhosis in 21.8% of F 4 patients over a follow-up of 2 years. These findings are close to what we found at 3 years, where cirrhosis has been reversed in 234 (25.2%) patients.…”
Section: Discussionmentioning
confidence: 99%